Learning Business English in China : The Construction of Professional Identity - Zhang, Zuocheng (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book analyses the learning experiences of students of Business English at a Chinese university. It addresses several topical issues in English for Specific Purposes (ESP) education and Business English teaching, including how ESP students learn, how they develop multiple identities. In particular, it focuses on their professional identity in the classroom, and how these identities are transferred to the workplace. This allows the author to present a model of learning Business English that corresponds to the lived experiences of students in China, but which can also be applied to other ESP learner contexts. In doing so, he demonstrates how to research the professional identity of ESP learners from multiple perspectives, and contributes to the validity of research on language learning and learner identity. This book will appeal to scholars of English for Specific Purposes, Second Language Acquisition, and TESOL Education. Zuocheng Zhang is Senior Lecturer in TESOL Education at the University of New England, Australia. His publications include monographs and textbooks on Business English and business discourse.